Effect of Bamboo Flour on Flame Retardancy and Smoke Suppression of Polypropylene/Ammonium Polyphosphate Composites - Liu, Yide; Li, Hongzhou; Chen, Qinghua; Luo, Fubin; Cao, Changlin (Frontiers in Materials, 2020)
In this paper, the flame retardant PP composites were prepared by melt blending. APP and bamboo flour are selected as flame retardant and smoke suppressant of the composite material. Among them, bamboo flour as a synergist can effectively improve the flame retardancy and smoke suppression effect of PP/APP composites. The effects of bamboo flour on the mechanical properties, crystallization behavior, thermal degradation, flame retardancy, and especially the smoke suppression effect of PP/APP composite materials were studied. TGA, LOI, cone calorimetry, SEM and other characterization methods were used to study the thermal stability, flame retardancy and combustion characteristics of the composites and the microscopic morphology of carbon residue. Experimental results show that when the total addition amount of APP/bamboo flour (2:1) in PP55/APP30/BF15 composite is 45%, the residual carbon has more specific surface area and micro-pores, which makes the composite have the best smoke suppression effect. The PHRR of the PP55/APP30/BF15 composite was reduced to 308.2 kW/m2 and the amount of carbon residue is 25%. The continuous carbon layer formed during combustion can effectively protect the matrix material and prevent heat transfer.